The Costs of Corruption for the Poor—The Energy Sector - Lovei, Laszlo (World Bank, Washington, DC, 2012)
In recent years the fight against corruption has assumed a key place in development policy, as a way of strengthening economic growth and helping civil society and democracy to function. Corruption not only stifles growth. It also perpetuates or deepens inequality, as the few amass power and wealth at the expense of the many. The energy sector lends itself to corrupt practices. This is a result both of its traditional institutional arrangements-dominated by state monopolies controlling oil, gas, or electricity-and of the sheer amount of cash it can generate. Corruption in energy takes many forms, from petty corruption in meter reading and billing to grand corruption in the allocation of lucrative monopolies. These practices differ in scale but contribute to the same results-weak operational and financial performance and, for the poor in particular, declining service quality or reduced chances of ever accessing network services. The answer to corruption is continuing reform, to reduce the incentive and potential to capture monopoly rents and to increase the transparency of public and private transactions, regulatory structures, and decision-making processes.